Konstruksi Cerita Tolire Gam Jaha Sebagai Sumber Belajar Sejarah Lisan - Zulkifli Zulkifli; Hi. Thalib Abas (Peneliti.net, 2022)
Tolire Gam Jaha village which is currently located in the Takome village, West Ternate district and this has become a human memory to this day that the village in ancient times caused the village to sink because it got a curse or disaster because it passed the provisions in conducting a traditional party which then happened. and finally the Tolire village sank and now leaves a legend. Therefore, in this study, to find out how far the students know about